Karakteristik Penggunaan Limbah Serbuk Kaca pada Campuran Aspal Laston (AC-BC) Terhadap Parameter Marshall - Syafi, Ilham Maulana; Hartatik, Nurani; Rizkiardi, Aditya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The increasing volume of transportation users annually has had an unstable impact on the quality of infrastructure construction, particularly on asphalt roads. Therefore, there is a need for monitoring to effectively and efficiently address damages to asphalt roads. One method of maintenance or repair for asphalt pavement that exceeds the planned lifespan in the Asphalt Concrete Binder Course (AC-BC) layer is through the diversion of common filler materials using the Marshall method. The researcher aims to explore the substitution of common filler materials, one of which involves utilizing waste glass powder to enhance layer stability. The waste glass powder material utilized is sourced from the production remnants of CV Sari Jaya Aluminum, located in Mojokerto. The research aims to investigate the impact of waste glass powder on Marshall parameters AC-BC Laston layer. The optimal and most efficient outcome obtained from the use of waste glass powder filler influence is a filler variation level of 2.5% with a planned asphalt content of 6.0%. All the obtained Marshall characteristic parameter results have met the requirements of the General Specification of Bina Marga (revision 2) Year 2018.